Unusual functions of insect vitellogenins: minireview - Kodrík, Dalibor; Čapková Frydrychová, Radmila; Hlávková, Daniela; Habuštová, Oxana; Štěrbová, Helena (Physiological research, 2023)
Insect vitellogenins are an intriguing class of complex proteins. They primarily serve as a source of energy for the developing embryo in insect eggs. Vitellogenesis is a complex hormonally and neurally controlled process that command synthesis of vitellogenin molecules and ensures their transport from the female fat bodies or ovarial cells into eggs. The representatives of all insect hormones such as juvenile hormones, ecdysteroids, and neurohormones participate in vitellogenesis, but juvenile hormones (most insect species) and ecdysteroids (mostly Diptera) play the most important roles in the process. Strikingly, not only insect females, but also males have been reported to synthesize vitellogenins indicating their further utility in the insect body. Indeed, it has recently been found that vitellogenins perform a variety of biological functions in the insect body. They participate in defense reactions against entomopathogens such as nematodes, fungi, and bacteria, as well as against venoms such as the honeybee Apis mellifera venom. Interestingly, vitellogenins are also present in the venom of the honeybee itself, albeit their exact role is unknown; they most likely increase the efficacy of the venom in the victim's body. Within the bee's body vitellogenins contribute to the lifespan regulation as anti-aging factor acting under tight social interactions and hormonal control. The current minireview covers all of these functions of vitellogenins and portrays them as biologically active substances that play a variety of significant roles in both insect females and males, and not only acting as passive energy sources for developing embryo.
Keywords: Vitellogenins; Insecta; Juvenile Hormones; Male; Animals; ekdysteroidy; Ecdysteroids; Female; mužské pohlaví; ženské pohlaví; vitelogeniny; juvenilní hormony; hmyz; zvířata; ovarium; Ovary